Draft Annual Plan 1987-88 Vol. IV (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1986)
Recently hostel building has been got constructed for 54 students only against the sanctioned strength of 180. Moreover, ho separate hostel accommodation is available for Women candidates of Architectural Engineering course being run at Government Polytechnic for Boys, Ambala City.
Planning Department, Government of Haryana